1962
DOI: 10.1111/j.1550-7408.1962.tb02647.x
|View full text |Cite
|
Sign up to set email alerts
|

Schizonts and Microgametocytes of Eimeria auburnensis Christensen and Porter, 1939, in Calves

Abstract: SYNOPSIS. Schizonts were found in the middle and lower third of the small intestine of two calves killed 12 and 14 days after they had been inoculated with pure cultures of oocysts of Eimeria auburnensis. The schizonts ranged from 78 to 250 μ long by 78 to 150 μ wide (mean 92 by 139.9 μ). They were usually located deep in the lamina propria near the muscularis mucosae instead of in the villi where most schizonts of Eimeria bovis are found. The schizonts of E. auburnensis resembled the previously described lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1967
1967
1990
1990

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Davis and Bowman (1962) (1961) reported that 4 calves 1-6 weeks old inoculated with 100,000-750,000 oocysts discharged moderate to high numbers of oocysts (about 14,000-200,000 per gram of feces); one had severe diarrhea 18-20 days after inoculation, 2 had mild diarrhea 18-19 days after inoculation, and one showed no signs of coccidiosis. Davis and Bowman (1962) reported that a month-old calf had diarrhea 6-12 days after inoculation; at autopsy on the 12th day, its small intestine was edematous 7 m anterior to the ileocecal valve.…”
Section: S the Coccidiax Parasites Of Ruminantsmentioning
confidence: 99%
“…Davis and Bowman (1962) (1961) reported that 4 calves 1-6 weeks old inoculated with 100,000-750,000 oocysts discharged moderate to high numbers of oocysts (about 14,000-200,000 per gram of feces); one had severe diarrhea 18-20 days after inoculation, 2 had mild diarrhea 18-19 days after inoculation, and one showed no signs of coccidiosis. Davis and Bowman (1962) reported that a month-old calf had diarrhea 6-12 days after inoculation; at autopsy on the 12th day, its small intestine was edematous 7 m anterior to the ileocecal valve.…”
Section: S the Coccidiax Parasites Of Ruminantsmentioning
confidence: 99%